Student mobility in Ireland and Northern Ireland - Smyth, Emer; Darmody, Merike (ESRI, 2023)
There has been an increasing focus in policy development internationally and in Ireland on the globalisation of higher education and student mobility. Consequently, a growing body of international research has focussed on the drivers of, and barriers to, studying abroad. Previous studies on this topic have highlighted a number of macro-, meso-, and micro-level factors that shape students’ experiences. However, there has been relatively little systematic research on the institutional factors which potentially influence student mobility between Ireland, Northern Ireland and Britain. This study focuses on mobility for a whole undergraduate course (rather than mobility for an academic year or semester). It draws on administrative data, Central Applications Office (CAO) microdata, interviews with key stakeholders and a consultation event with stakeholders to address the following research questions: What is the level of student mobility between Ireland and Northern Ireland (and between NI and the other countries of the UK)? How has this changed over time, in particular during the pandemic? What factors are associated with student mobility? To what extent is there potential to increase student mobility across the island? And is this seen as a desirable objective by stakeholders? MAIN FINDINGS In 2020/21, 1,170 students from Ireland went to study in Northern Ireland while 1,255 students from Northern Ireland attended a higher education institution (HEI) in Ireland. Students from Ireland made up 2.4 per cent of students in Northern Ireland while students from Northern Ireland made up only 0.6 per students in Ireland. More students from Ireland go to study in the rest of the UK than in Northern Ireland, with numbers staying stable over time at just over 4,000 each year. There is a relatively large outflow of students from Northern Ireland to the rest of the UK (RUK) (13,685 in 2020/21), reflecting at least in part high levels of competition for places, with very little mobility in the opposite direction. Only a minority of applicants from Northern Ireland or RUK make it all the way through to being offered and accepting a place in Irish HEIs. This is partly related to these candidates being less likely than those from Ireland to meet minimum matriculation requirements. This could reflect the nature of qualification recognition and/or applicants having less information about course requirements outside the jurisdiction. However, even when offered a place, those from Northern Ireland and RUK are less likely to accept the place, suggesting the impact of differential timing of course offers and/or using an application elsewhere as a safety-net in securing a high-demand course. Similarly, acceptance rates for UK universities are lower for Irish applicants than for those from the UK. Decision-making processes around where to study reflect the complex interaction of guidance provided at school level, the recognition of qualifications, tuition/registration fees and financial supports, and other living costs. IMPLICATIONS FOR POLICY AND PRACTICE Stakeholders highlight the value of mobility for students themselves, for higher education institutions and for enhancing cross-border cooperation. The findings indicate: There is potential for school-based guidance to provide greater awareness of options in other jurisdictions, a process which can be usefully supported by outreach work by HEIs. There is a case to reexamine CAO point equivalences for A-levels, given the very small group of Northern Ireland candidates who take four Alevels, and to look at modern foreign language requirements (in courses where such skills are not critical), given much lower take-up of modern foreign languages in Northern Ireland. Decisions about where to study take place, for students, against a broader backdrop of rising costs and access to differential levels of financial supports and, for HEIs, funding challenges. It is difficult to divorce the matter of student mobility from these wider issues of the adequacy of financial supports for students and funding levelsfor the higher education sector. For example, the cap on places in Northern Ireland could usefully be revisited to enhance higher education participation in general and cross-border mobility. Overall, the study findings highlight the need for coordinated interventions across different levels of both systems if student mobility is to be an important policy goal.